2020
DOI: 10.1002/ijgo.13452
|View full text |Cite
|
Sign up to set email alerts
|

Status of institutional‐level respectful maternity care: Results from the national Ethiopia EmONC assessment

Abstract: Objective To assess the availability of an institutional‐level respectful maternity care (RMC) index, its components, and associated factors. Methods A cross‐sectional study design was applied to a 2016 census of 3804 health facilities in Ethiopia. The availability of an institutional‐level RMC index was computed as the availability of all nine items identified as important aspects of institutional‐level RMC during childbirth. Logistic regression analysis was used to identify factors associated with availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…These findings align with a 2015 systematic review by Bohren et al which found that health system factors, such as a lack of privacy or staffing shortages, can be experienced directly by women as mistreatment [ 3 ]. Our study’s findings are consistent with the global literature that suggests mistreatment is not merely an interpersonal problem, but is also driven by health system inadequacies that affect clients and providers alike [ 10 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…These findings align with a 2015 systematic review by Bohren et al which found that health system factors, such as a lack of privacy or staffing shortages, can be experienced directly by women as mistreatment [ 3 ]. Our study’s findings are consistent with the global literature that suggests mistreatment is not merely an interpersonal problem, but is also driven by health system inadequacies that affect clients and providers alike [ 10 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 89%